The Role Of Continuous Improvement Of University Education Using The Deming Model In Supporting Com- petitive Advantage/Exploratory Research On The Middle Technical University/Baghdad - Aboodi, Basima (Opción, 2019)
The current study aims to provide a conceptual and practical framework on the role of continuous improvement of university education in achieving com- petitive advantage through the Central University’s endeavor to make ad- justments and improvements in its educational work in the field of scientific, technical and administrative development to achieve a globally differentiated arrangement. In order to achieve this, a random sample of a number of university formations (Institute of Technology, Institute of training of technical trainers, Institute of Technical Administration) has been selected, of which 146 are members of the study community, represented by faculty members. The resolution was used as a tool to collect the Study Data and is made up of (22) paragraphs (12) of the Deming approved paragraph (Planning, Do, Check, Act) and (10) a paragraph of competitive advantage, the data was pro- cessed using statistical software (SPSS v23). based on the analytical descrip- tive approach to testing the hypotheses of the study, one of the most important findings of the study was the strong correlation between the study variables with the industry in question, in the light of the findings, the study made a series of recommendations to guide the promotion of competitive advantage in the university.